Dietary black-grained wheat intake improves glycemic control and inflammatory profile in patients with type 2 diabetes: a randomized controlled trial - Liu Y; Qiu J; Yue Y; Li K; Ren G (Dove Medical Press, 2018)
Yanping Liu,1,* Ju Qiu,2,* Yanfen Yue,3 Kang Li,3 Guixing Ren41Department of Nutrition, Peking Union Medical College Hospital, Beijing, 2Institute of Food and Nutrition Development, Ministry of Agriculture, Beijing, 3Department of Nutrition, Pinggu Hospital of Traditional Chinese Medicine, Beijing, 4Institute of Crop Sciences, Chinese Academy of Agricultural Sciences, Beijing, China *These authors contributed equally to this workIntroduction: Although black-grained wheat (BGW) is recognized as a nutritional food for humans in China, it has yet to be utilized well for industrial applications, which can be attributed to the limited research data available on its health benefits. Thus, the hypothesis was tested that a daily substitution of BGW for a partial staple food would improve glycemia and inflammatory profile of type 2 diabetes mellitus (T2DM) patients by a randomized controlled trial. Materials and methods: A total of 120 patients were randomly divided between control group (diet control and nutritional education) and BGW group (daily substitution of BGW for a partial staple food). Results: Based on the significant difference between BGW and control groups (P<0.05), the primary outcomes were that BGW treatment in diet resulted in a significant lowering of glycated albumin (GA, 18.05 to 16.06 mmol/L) level in T2DM patients after a 5-week intervention, and this treatment regimen was much more efficient than the strategy of diet control alone. In addition, BGW supplementation prevented the increase in tumor necrosis factor (TNF)-α and interleukin (IL)-6 induced by T2DM. There were no significant differences in blood glucose, glycated hemoglobin or insulin levels between the 2 groups. The subgroup analyses of the BGW daily intake showed that, except the TNF-α, significant improvements in GA and IL-6 were observed when the BGW intake dose was >69 g/day.Conclusion: These findings support the hypothesis that BGW may improve glycemia and the inflammatory profile in T2DM patients. Keywords: black-grained wheat, glycated albumin, tumor necrosis factor-α, interleukin-6